(untitled) (Romanian Journal of Analytic Philosophy, 2025)
This paper addresses our difficulty in grasping how something like consciousness could emerge from the processes of our brain, aiming to explain the intuitions that underlie this struggle. I start with an investigation of materialism, revealing that its supporters often have deep-seated dualist intuitions implicitin some of the language they use. I then question whether we can warrant the claim that conscious experience is fundamentally different from non-conscious phenomena with respect to causal powers and causal roles. I identify the derivability gap as the reason behind our intuitive struggles, explaining how these intuitions make it difficult to accept a materialist view of consciousness. Lastly, I explain why we hold onto these intuitions. Instead of seeking a socio-cultural origin for our dualist intuitions about the mind-body problem, I suggest we examine our intuitive grasp of the physical world, arguing that our tendency to see things in binary on/off forms extends beyond our grasp of consciousness. I propose that we consider whether the same simplifying principle that aids our understanding of unobservables might also influence how we conceive consciousness. I conclude that our lack of direct exposure to its complexity may underlie our binary understanding of life and non-life, which we extend to the contrast between material and non-material.